A creative learning ecosystem, quality of education and innovative capacity: a perspective from higher education - Crosling, Glenda *; Nair, Mahendhiran; Santha Vaithilingam (Teylor & Francis, 2014)
Globally, governments recognize the importance of creativity and innovation for sustainable socioeconomic development, and many invest resources to develop learning environments that foster these capacities. This paper provides a systematic framework based on Nair’s Innovation Helix model for studying the factors of a country’s creative learning ecosystem (CLE), the quality of its education system (QES), and its innovative capacity (IC). The CLE factors are infrastructure/infostructure (physical and digital infrastructure), intellectual capital, interaction, integrity systems, incentives, and institutions. Using a composite CLE index for 113 countries, the findings indicate a strong correlation between a country’s CLE, QES and IC. Through brief case studies of countries that measure highly in CLE, QES and IC, this study points out their higher education strategies and their best practices for other countries to emulate, in order to facilitate creativity and innovation through higher education.